SAEB 2021 and the teaching-learning process through ICTs – a positive dialogue in the pandemic context - Wernek , Fabio Reith; Nascimento, Jussara Cassiano (Seven Editora, 2023)
This article is situated in the context of the practices developed during the pandemic period, when there was a closure of schools in the face-to-face mode and a forced and urgent migration to the remote mode, all over the world. Through the analysis of the data offered by the SAEB before 2021 and the updated data, it is clear that the effort made by the teachers and managers of Colégio Brigadeiro Newton Braga (CBNB) obtained positive results, although recognizing a series of difficulties, among them that of involving as many students as possible with remote teaching, in the initial period of the pandemic. The theoretical and methodological foundation is mirrored in studies by Benjamin (1996), Certeau (1994), Bonamino (2016), Muller (2018), among others. The results indicate that the effort of CBNB teachers and managers to migrate to remote teaching as soon as possible had positive effects. However, we identified that there is still a long way to go in search of a better didactic use of network environments and appropriate use of digital technologies within the institution. DOI: https://doi.org/10.56238/devopinterscie-068